A Critical Analysis of Ācārya Buddhaghosa's attitude towards Women (Bodhi Path, 2021)
Woman has a huge contribution not only in the origin of mankind, but also in building the society. The study of the status and role of women is very important during the study of any social setup. If we review the social status of women in ancient Indian society, then it can be easily noticed that the male-dominated society was often failed in providing proper status to women and accepting their participation in the construction and development of the society. Ancient Indian authorship have also made no remarkable efforts to strengthen the social status of women. Women have always been portrayed as a dependent and a burden of men. In almost every religion and sect of the world, women are held in chains of restrictions and women have not been able to break those chains completely till the date. They have been kept marginalized in the records (religious texts) of almost every religious tradition. Study of social status of women based on Pāḷi-Aṭṭhakathā literature by Indian scholars and historians is almost negligible. So, the main objective of this paper is to critically analyze the status of women described in Suttanipāta-Aṭṭhakathā. By doing so, the social-status of women around 4th–5th century AD can be assessed and at the same time we can also infer what was the attitude of the great Buddhist scholar and litterateur Buddhaghosa towards women. Keywords : Ācārya Buddhaghosa, Pāḷi Aṭṭhakathā literature, Status of Women
Keywords: Ācārya Buddhaghosa, Pāḷi Aṭṭhakathā literature, Status of Women